Sayyid Mawdudi’s tafsir and modern challenges: an analysis - Osmani, Noor Mohammad; Rahman, Mizanur; Ali, Md Yousuf (IIUM Press, 2023)
Sayyid Abul A‘la Mawdudi (1903-1979) lived at a time when Islam was attacked from many corners of the world, from Western scholars, orientalists, modern scholars, Muslim apologists, anti-hadith movement and so on. The Western scholars do not regard the Qur’an to be divine words. To them, Muhammad (PBUH) had just copied the Qur’an from biblical texts. They only regard the Bible to be the divine words. Some modern scholars submitted to the limited ability of rationality and rejected many Qur’anic issues which are based on supernatural abilities and the miracles of the Prophet. Anti-Hadith scholars rejected the authenticity and the validity of the Prophetic traditions. To them, only Qur’an to be followed and nothing else. Sayyid Mawdudi dealt with all these challenges strongly and many other anti-Islamic and anti-Qur’anic forces. This study follows textual studies based on the Qur’an, and the Tafhim al-Qur’an, the famous tafsir of Mawdudi and his other related writings. The study concluded that a reader should not get biased by preconceived notions while reading the Qur’an. Rather he should keep his heart and mind open in dealing with the Qur’anic issues and principles. It will open the doors of divine guidance for all sound-minded people.